2005
DOI: 10.1002/jccs.200500147
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Baicalin by High Performance Liquid Chromatography Coupling with Flow Injection Chemiluminescence Detection

Abstract: A new method for the determination of baicalin in Scutellariae Radix extract and its preparations by high performance liquid chromatography (HPLC) coupling with flow injection chemiluminescence detection (FIA-CL) has been developed. The method was based on the chemiluminescence reaction of potassium permanganate with baicalin in nitric acid medium; the CL intensity can be enhanced by formaldehyde. In this study, the conditions of chemiluminescence and chromatography were examined, and the schematic diagram of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many researchers have reported emission spectra consisting of a single broadly distributed band with an apparent maximum intensity between 610 nm and 750 nm. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] This red emission has often been attributed to the production of singlet oxygen, 3,[9][10][11][12][13][14][15][16][17][18][23][24][25] but the spectral distribution for singlet oxygen (bands at 633, 703 and 1268 nm) 26,27 is unlike that observed for acidic potassium permanganate chemiluminescence. 28 Many other researchers have suggested that the chemiluminescence emanates from a manganese(II) species.…”
mentioning
confidence: 99%
“…Many researchers have reported emission spectra consisting of a single broadly distributed band with an apparent maximum intensity between 610 nm and 750 nm. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] This red emission has often been attributed to the production of singlet oxygen, 3,[9][10][11][12][13][14][15][16][17][18][23][24][25] but the spectral distribution for singlet oxygen (bands at 633, 703 and 1268 nm) 26,27 is unlike that observed for acidic potassium permanganate chemiluminescence. 28 Many other researchers have suggested that the chemiluminescence emanates from a manganese(II) species.…”
mentioning
confidence: 99%